2020
DOI: 10.3389/fbioe.2020.00792
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Hydrogel Microparticles With Three-Dimensional Liver Progenitor Cell Spheroids

Abstract: The study of the liver progenitor cell microenvironment has demonstrated the important roles of both biochemical and biomechanical signals in regulating the progenitor cell functions that underlie liver morphogenesis and regeneration. While controllable twodimensional in vitro culture systems have provided key insights into the effects of growth factors and extracellular matrix composition and mechanics on liver differentiation, it remains unclear how microenvironmental signals may differentially affect liver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…These methods show low throughput and low reproducibility due to the difficulty of changing clean culture media and the problem of spheroid loss. There is also a method for aggregating and culturing cells in 3D using mesh-type structures such as aggrewell 6 and matrix-free microwell systems 7 . However, this method is a scaffold-free type and aggregated cells in media easily moved in media.…”
Section: Introductionmentioning
confidence: 99%
“…These methods show low throughput and low reproducibility due to the difficulty of changing clean culture media and the problem of spheroid loss. There is also a method for aggregating and culturing cells in 3D using mesh-type structures such as aggrewell 6 and matrix-free microwell systems 7 . However, this method is a scaffold-free type and aggregated cells in media easily moved in media.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study suggested an in vitro model of 3D LPCs spheroidal cultures with integrated polyethylene glycol hydrogel microparticles for the internal presentation of modular microenvironmental cues, which could be applied to the engineering of instructive microenvironments of transplanted LPCs. In this study, modification of the microparticles with TGF-β1 or heparin influences the behavior of LPCs toward BECs differentiation [ 64 ]. However, until now there has been limited data concerning engineering of 3D culture models of LPCs through the tunable presentation of microenvironmental stimuli.…”
Section: Regenerative Medicine and Cell Transplantation For Esldmentioning
confidence: 99%
“…[ 22 ] As in other organ systems, 3D culture of liver more closely mimics in vivo conditions, and we have observed that differentiation of BMEL aggregates can also be affected by modifying the 3D environment. [ 23 ] To date, the relationships between geometry, mechanical signaling, and liver progenitor fate specification in 3D has not yet been characterized.…”
Section: Introductionmentioning
confidence: 99%